VD_FINDINFO AF 2/14 - 5/2014 vom 19. Dezember 2014 - VD Tribunal cantonal (2014)
VERSEMENT EN MAINS D'UN TIERS, CURATELLE DE REPRÉSENTATION, FILIATION, ACTIVITÉ LUCRATIVE | 7 al. 1 LAFam, 8 LAFam, 9 LAFam